The Presence of Chewing Lice (Insecta: Phthiraptera) Species on Wild Quails (Coturnix coturnix) - Aksin, Nursel (Medwell Online, 2010)
This research was conducted to determine species of chewing lice (Phithiraptera) on wild quails (Coturnix coturnix). For this purpose, 30 wild quails obtained in different areas of Elazig province (the Eastern Anatolian region) of Turkey in 2006 and 2008 during the hunting season between August-October were examined in terms of ectoparasites. It was established that 19 (63.33%) wild quails were infested with at least one chewing lice species. A total of 53 chewing lice were collected from the infested quails and the diagnosis of them led to the discovery of three different species. Of the infested quails, 6 (31.58%) were found to have Menacanthus abdominal is, 12 (63.15%) were found to have Cuclotogaster cinereus and 1 (5.27%) was found to have Goniodes astrocephalus. In this study, the evidence of Menacanthus abdominalis, Goniodes astrocephalus and Cuclotogaster cinereus on wild quails is reported for the first time in Turkey.
Keywords: Chewing lice; quail; Coturnix coturnix; M. abdominalis; C. cinereus and G. astrocephalus; Turkey